Pengaruh Terapi Layering Krim Cysteamine 5% dan Asam Traneksamat 3% terhadap Skor Masi Pasien Melasma - Putti Fatiharani Dewi; Ummi Rinandari; Fiska Rosita; Arie Kusumawardani; Nugrohoaji Dharmawan (Syntax Corporation Indonesia, 2021)
Melasma is a hypermelanosis disorder that arises typical of areas of the skin that are often exposed to sunlight. Melasma therapy is relatively difficult because there is often chronicity in melasma. Until now therapy with Kligman formula is still an option, but kligman formula has some side effects, especially for long-term use. Cysteamine works by inhibiting the enzyme tyrosinase. Traneksamat acid works by inhibiting the activity of plasmin in keratinocytes known as stimulators of tyrosinase activity The purpose of the study proved and analyzed the effectiveness of cysteamine cream layering therapy 5% and tranexilic acid 3% compared to kligman formula modification in melasma sufferers to improve MASI score. Experimental research method, pre and post control group design double-blind randomied controlled trial with 28 samples of melasma patients namely group A using layering cysteamine cream 5% and traneksamat acid 3% compared to the group of patients melasma i.e. group A using layering cysteamine cream 5% and traneksamat acid 3% compared to the group of patients. Assessment and measurement of the effectiveness of therapy is carried out during weeks 0, 2, 4 and 8, with an assessment of MASI score. The analysis used is the t-pair test and the Wilcoxon test. Statistical tests are considered meaningful if p<0.05. The results of the study decreased the difference in MASI score in group A obtained in week 4 and week 8, while group B in week 8. The difference in the difference in MASI score change between group A and group B in weeks 4 and 8 indicates a significant difference (p=0.025 and p=0.003). Conclusion of 5% layering cysteamine therapy and 3% tranex acid indicates a decrease in the difference in MASI score earlier than modified Kligman cream therapy.